Decoding Predatory Publishing practices for Academia - Nayanthara, S.; Sulochana, Anila (Journal of Information and Knowledge, 2023)
Predatory or deceptive publishing is still a persistent issue in scholarly communication. A large number of predatory journals are being published, and it is essential to keep them in check as the potential harm they could do to the scientific discourse is enormous. With the Open Science Framework (OSF) project titled "Decoding Predatory Publishing Practices for Academia (DePA)," the authors try to equip users to identify potential predatory journals and endorse ethical and quality publishing. The project will consist of training materials and a rubric developed to examine the quality of an open-access scientific journal by combining the publisher and individual journal aspects. The project includes a rubric consisting of different aspects regarding publication in scientific journals, quantifying the quality of the publishing practices adopted by these journals. Predatory or deceptive publishing is still a persistent issue in scholarly communication. For instance, deceptive publishers could hold the unpublished manuscript indefinitely, and little can be done if the author has signed a copyright transfer agreement. We can reduce the impact of predatory publishers by aiding the scholar community with simple and easy-to-understand devices that help them analyse the journals and publishers themselves. This could be part of the orientation at a researcher’s, library’s, or mentor’s level.